BRAND EXPERIENCE FOR LUXURY CARS: A CASE STUDY OF VIETNAMESE CONSUMERS - TRAN, HANH UYEN DAM (2012)
This dissertation would not have been possible without the guidance and the help of several individuals who in one way or another contributed and extended their valuable assistance in the preparation and completion of this study. First and foremost, I would like to express my very great appreciation to Dr Sally McKechnie, my research supervisor, for her patient guidance, enthusiastic encouragement, useful critiques and offering suggestions for improvement of this research work. Secondly, I am deeply indebted to the Department of Marketing for providing the valuable knowledge during my study and giving me permission to commence this dissertation. I have furthermore to extend my thanks to the University of Nottingham for their outstanding study environment. Finally, I wish to thank my dearest parents, siblings and friends for their support and encouragement.